2018
DOI: 10.3389/fnmol.2017.00421
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Gone Rogue: Impacts on Psychiatric Disorders across the Lifespan

Abstract: Microglia are the predominant immune response cells and professional phagocytes of the central nervous system (CNS) that have been shown to be important for brain development and homeostasis. These cells present a broad spectrum of phenotypes across stages of the lifespan and especially in CNS diseases. Their prevalence in all neurological pathologies makes it pertinent to reexamine their distinct roles during steady-state and disease conditions. A major question in the field is determining whether the cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
147
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(156 citation statements)
references
References 354 publications
3
147
0
Order By: Relevance
“…Differences in microglial number, morphology, and gene expression were also reported between sexes (Schwarz et al , ; Crain et al , ; Lenz et al , ; Pimentel‐Coelho et al , ; Butovsky et al , ; Dorfman et al , ; Hanamsagar et al , ; Krasemann et al , ). Adequate microglial functions are crucial for plasticity and behavioral adaptation to the environment (Salter & Stevens, ; Tay et al , ). Throughout life, microglia contribute to neurogenesis, neuronal circuit shaping, vascular formation and remodeling, and maintenance of homeostasis (Tay et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in microglial number, morphology, and gene expression were also reported between sexes (Schwarz et al , ; Crain et al , ; Lenz et al , ; Pimentel‐Coelho et al , ; Butovsky et al , ; Dorfman et al , ; Hanamsagar et al , ; Krasemann et al , ). Adequate microglial functions are crucial for plasticity and behavioral adaptation to the environment (Salter & Stevens, ; Tay et al , ). Throughout life, microglia contribute to neurogenesis, neuronal circuit shaping, vascular formation and remodeling, and maintenance of homeostasis (Tay et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…During aging and in diseases, these cells may become reactive or impaired in their surveillance and phagocytosis (Streit, ; Koellhoffer et al , ; Spittau, ). Microglial contribution to diseases is associated with compromised physiological roles (e.g., in synaptic maintenance and plasticity; Tay et al , ) and processes that are adaptive in the healthy brain, yet leading to cell death and tissue damage in pathological settings (e.g., excitotoxicity, oxidative stress, and inflammation; Weil et al , ). Microglial reaction can be triggered by any kind of insults or disturbances to the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have reported a higher rate of maternal autoimmunity in children with ASD and Tourette syndrome . It has been hypothesized that maternal autoimmunity and other maternal immune factors may pose a risk to the fetus through ‘maternal immune activation’, whereby the inflammatory milieu in utero is thought to result in epigenetic alteration of expression of genes involved in neuronal development and/or activation of the resident immune cells of the brain, the microglia . Although there is robust animal model support for the maternal immune activation hypothesis, evidence in humans is lacking, and longitudinal studies are required.…”
mentioning
confidence: 99%
“…The 15q11.2(BP1-BP2) deletion is not solely associated with schizophrenia, it also markedly increases risk for autism spectrum disorders 63 , ADHD and developmental delay 64 , and epilepsy 65 . Whether altered microglia functioning due to Cyfip1 haploinsufficiency, impacting on adult hippocampal neurogenesis, also plays a part in these disorders is an open question, but all have been associated with alterations in immune system and microglia functioning 66,67 . Moreover, as noted previously, a number of schizophrenia risk genes, including DISC1 37 , SREB2/GPR85 38 , CACNA1C 39,40 DGCR8 41 , and miR137 42 , have also been shown to modify adult hippocampal neurogenesis in model systems.…”
Section: Discussionmentioning
confidence: 99%